1999
DOI: 10.1016/s0035-9203(99)90379-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of directly observed treatment (DOT) for patients with pulmonary tuberculosis in Thailand

Abstract: While directly observed treatment (DOT) has been recommended as the standard approach to tuberculosis control, empirical data on its feasibility and efficiency are still scarce. We conducted a controlled trial of DOT at 15 health care facilities at various levels of the government health care system in Thailand. A total of 836 patients diagnosed between August 1996 and October 1997 were randomly assigned to be treated either under DOT or self-supervised using monthly drug supplies (SS). Options for treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 14 publications
0
86
2
2
Order By: Relevance
“…22 The TB cure rate achieved by this study were higher than the rates obtained by other national surveys with patients coinfected with HIV who achieved TB cure rates below 58.8%. [23][24][25] However, the success rates recorded for both groups of patients in the present study were lower than those observed in previous studies [26][27][28][29][30][31][32] of populations, containing varying percentages of HIV-infected patients, that had been treated under a directly observed therapy (DOT) Home-based care program for patients coinfected with tuberculosis and human immunodefi ciency virus program. Furthermore, the number of patients who attained a cure under either treatment program in the present survey did not reach the 85% standard set by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 70%
“…22 The TB cure rate achieved by this study were higher than the rates obtained by other national surveys with patients coinfected with HIV who achieved TB cure rates below 58.8%. [23][24][25] However, the success rates recorded for both groups of patients in the present study were lower than those observed in previous studies [26][27][28][29][30][31][32] of populations, containing varying percentages of HIV-infected patients, that had been treated under a directly observed therapy (DOT) Home-based care program for patients coinfected with tuberculosis and human immunodefi ciency virus program. Furthermore, the number of patients who attained a cure under either treatment program in the present survey did not reach the 85% standard set by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 70%
“…Moreover, it has its economic and psychosocial implications in the developing world [9,17]. False positivity in PCR can be minimised by the adequate training of personnel in molecular methods and preventing laboratory-introduced contamination.…”
Section: Discussionmentioning
confidence: 99%
“…It is true that some small pilot projects (none of which have monitored relapse or development of drug resistance) using family observation, combined with intensive supervision and home visits, have achieved high cure rates. [12][13][14] However, other studies have reported that family observation yields lower cure rates and much higher default rates than observation by someone outside the family, 15 and results in a substantial proportion of treatment being unobserved and much higher rates of non-adherence. In practice, where family observation is allowed, patients are often merely handed medicines and told to have their spouse watch them take the pills, a practice that is inconsistent with WHO guidelines specifying that treatment observers be trained and supervised by the health-care system.…”
Section: Family Observation Is a Seductive But Risky Conceptmentioning
confidence: 99%